Free Speech: A Very Short Introduction - Warburton, Nigel (New York Oxford University Press, 2009)
Voltaire's comment--"I disapprove of what you say, but I will defend to the death your right to say it"--is frequently quoted by defenders of free speech. Yet it is rare to find someone prepared to defend all freedom of speech, especially if the views expressed are obnoxious or obviously false. So where do we draw the line? How important is our right to freedom of speech? In this accessible and up-to-date Very Short Introduction, Nigel Warburton covers a wide range of controversial free-speech issues, from Holocaust denial and pornography to the status of modern copyright law. The book offers a concise guide to many of the vexing issues concerning our right to speak freely, including: Should a civilized society set limits on freedom of speech? How can we balance free speech with the sensitivities of religious and minority groups? How have digital technology and the Internet changed the debate?
Includes Index and Illustrations.
Keywords: Freedom of speech